2008
DOI: 10.1681/asn.2007101108
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of SNAT2 by Metabolic Acidosis Enhances Proteolysis in Skeletal Muscle

Abstract: Insulin resistance is a major cause of muscle wasting in patients with ESRD. Uremic metabolic acidosis impairs insulin signaling, which normally suppresses proteolysis. The low pH may inhibit the SNAT2 L-Glutamine (L-Gln) transporter, which controls protein synthesis via amino acid-dependent insulin signaling through mammalian target of rapamycin (mTOR). Whether SNAT2 also regulates signaling to pathways that control proteolysis is unknown. In this study, inhibition of SNAT2 with the selective competitive subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 32 publications
4
61
0
1
Order By: Relevance
“…Intriguingly, inducing either a "sepsis-like" state in rats by intraperitoneal injection of lipopolysaccharide (66) or muscle atrophy by spinal chord transection (26) markedly reduces the signaling capacity of the TOR pathway in skeletal muscle. Although these latter studies did not examine whether the observed defect in TOR signaling could be attributed to a loss in intramuscular glutamine, reducing the intramyocellular concentration of this amino acid by suppressing the activity or expression of SNAT2 not only enhances cellular proteolysis but impairs mTOR/S6K1 signaling in L6 muscle cells (28,29). It follows from these observations that the fidelity with which amino acids, such as leucine, can exert an influence on cell signaling is critically dependent on not only maintaining cellular hydration but preserving the transmembrane concentration gradient of glutamine and potentially that of other SNAT2 amino acid substrates, which, although regarded as nonessential, are physiologically indispensable from the perspective of preserving the primacy of leucine in terms of TOR signaling (9).…”
Section: Implication Of a Change In Transmembrane Amino Acid Distribumentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, inducing either a "sepsis-like" state in rats by intraperitoneal injection of lipopolysaccharide (66) or muscle atrophy by spinal chord transection (26) markedly reduces the signaling capacity of the TOR pathway in skeletal muscle. Although these latter studies did not examine whether the observed defect in TOR signaling could be attributed to a loss in intramuscular glutamine, reducing the intramyocellular concentration of this amino acid by suppressing the activity or expression of SNAT2 not only enhances cellular proteolysis but impairs mTOR/S6K1 signaling in L6 muscle cells (28,29). It follows from these observations that the fidelity with which amino acids, such as leucine, can exert an influence on cell signaling is critically dependent on not only maintaining cellular hydration but preserving the transmembrane concentration gradient of glutamine and potentially that of other SNAT2 amino acid substrates, which, although regarded as nonessential, are physiologically indispensable from the perspective of preserving the primacy of leucine in terms of TOR signaling (9).…”
Section: Implication Of a Change In Transmembrane Amino Acid Distribumentioning
confidence: 99%
“…An additional line of evidence that indicates a potential role for SNAT2 in amino acid signaling comes from the work of Bevington and coworkers, who have recently reported that incubation of muscle cells with a saturating dose of Me-AIB exerts a stimulatory effect on insulin-stimulated PI 3-kinase activity and PKB/Akt phosphorylation (29). In contrast, silencing SNAT2 expression using RNA interference had a suppressive effect on the lipid kinase activity of PI 3-kinase (29).…”
Section: A Role For Snat2 (System A) In Amino Acid Sensingmentioning
confidence: 99%
“…CKD It is well documented that myocyte growth is regulated by mTOR, at least partly through the PI3-K/PKB signalling pathway and this is probably the pathway that is stimulated in response to resistance exercise in vivo resulting in muscle hypertrophy 7 . Secondly, possibly through direct inhibitory effects of low pH on active amino acid transporters in skeletal muscle cells 6 , acidosis in CKD significantly depletes intramuscular pools of free amino acids, thus reducing capacity for protein synthesis, and impairing amino acid-dependent anabolic signalling through mTOR.…”
Section: Skeletal Muscle Abnormalities In Ckd Patientsmentioning
confidence: 99%
“…L-Leu) by exchanging intracellular non-essential amino acids (e.g. L-Ala) for extracellular L-Leu (Baird et al 2009;Evans et al 2008;Nicklin et al 2009). Indeed, failure of these gradients could explain depletion of a number of the amino acids observed in Figure 1 and Table 5.…”
Section: Amino Acid Depletionmentioning
confidence: 99%
“…2004), is strongly inhibited by acidosis (Baird et al 2006;Evans et al 2007;Evans et al 2008) and inhibited in CKD (Asola et al 2001). No change was seen in SNAT2 expression (Table 6), but studies in vitro have shown that acidosis directly inhibits this transporter protein (Baird et al 2006;Zhang et al 2011) independent of gene expression (Evans et al 2007;Evans et al 2008). However this inhibition by acid has previously only been studied acutely, and the corresponding chronic effects of acid on this transporter in the context of exercise and mechanical stress merit further investigation.…”
Section: Amino Acid Depletionmentioning
confidence: 99%